PENINGKATAN KEMAMPUAN GURU KELAS RENDAH DALAM MENGELOLA PROSES PEMBELAJARAN MELALUI SUPERVISI KLINIS MASA PANDEMI COVID-19 - Mulyadi, Muhammad (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was school action research (SAR) that raises how low-grade teachers can manage the learning process in classroom with the intention of improving the quality of learning that conducted in the classroom and the evaluation is carried out through clinical supervision activities by principle in the classroom during learning. This school action research was conducted at SD Negeri 1 Teros for 3 months starting from January to march 2022 by going through stages of the cycle. The aim of this school action research was to know how far the supervision that conducted by the principle followed by giving the coaching/treatment to teachers can improve the skill of the teachers to manage the learning process in the classroom. This school action research was conducted in 2 cycles, from the result of the action taken was proven can improve the skill of the teachers with achieve the ideal standard. In cycle I, the improving of teachers’ skill after conducted the clinical supervision and after giving the coaching about managing the learning process was just achieve about 50%, in cycle II it was improved to 100%. The average score obtained after conducted the clinical supervision in cycle I is 74.16 and improved at cycle II to 85.83, it means that there is an improvement of 11.76 and the level of completeness as group/classical in cycle I reached 50% and in cycle II improved to 100%. The result of this school action research showed that the coaching by principle can improve the skill of the teachers in managing the learning process in learning process.